Donor Darah Civitas Akademika STIE Kalpataru (Setetes Darahmu Mampu Selamatkan Mereka) - Bukhari Muslim (CV. Aksara Global Akademia, 2023)
The service activity carried out is in the form of a blood donation organized by the academic community of STIE Kalpataru Cibinong Bogor together with PMI Bogor Regency for the purpose of meeting the blood needs in Bogor Regency in particular, and in general it can also be used for other regions in Indonesia. This activity involves all parts of the academic community, including leaders, lecturers, staff and STIE Kalpataru students. PMI Bogor Regency appreciated this early activity very well, and they hope that this activity can be held routinely every year. This activity is intended as part of caring for others and an effort to uphold human solidarity.